Sample EPD 151 Syllabus_Fall 2009 - Kindschi, Amy; Wheeler, Diana; Vellardita, Lia (My University, 2009)
Syllabus used in EPD 151: Technical Information Resources, Fall 2009. Kurt F. Wendt Library, UW-Madison College of Engineering.
Keywords: syllabus; Engineering Professional Development; Technical Information Resources; EPD